2017
DOI: 10.1080/13506285.2017.1347590
|View full text |Cite
|
Sign up to set email alerts
|

How does information from low and high spatial frequencies interact during scene categorization?

Abstract: Current models of visual perception suggest that, during scene categorization, low spatial frequencies (LSF) are rapidly processed and activate plausible interpretations of visual input. This coarse analysis would be used to guide subsequent processing of high spatial frequencies (HSF). The present study aimed to further examine how information from LSF and HSF interact and influence each other during scene categorization. In a first experimental session, participants had to categorize LSF and HSF filtered sce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 47 publications
4
15
1
Order By: Relevance
“…Scene perception is understood as involving a coarse-to-fine processing sequence using both low spatial frequency cues (rapidly processed and allowing for parsing of global structure) and high frequency information (which is relayed more slowly to high-level areas; Kauffmann et al., 2014 ). The present study links the rapid processing of low frequency cues to the formation of categorical representations, supporting previous reports of coarse visual analysis as rapid and crucial to gist perception ( Kauffmann et al., 2017 ; Peyrin et al., 2010 ; Schyns and Oliva, 1994 ). On the other hand, high spatial frequency representations of scenes do not generalize to unfiltered stimuli, suggesting that they may encode low-level differences rather than a categorical response.…”
Section: Discussionsupporting
confidence: 90%
“…Scene perception is understood as involving a coarse-to-fine processing sequence using both low spatial frequency cues (rapidly processed and allowing for parsing of global structure) and high frequency information (which is relayed more slowly to high-level areas; Kauffmann et al., 2014 ). The present study links the rapid processing of low frequency cues to the formation of categorical representations, supporting previous reports of coarse visual analysis as rapid and crucial to gist perception ( Kauffmann et al., 2017 ; Peyrin et al., 2010 ; Schyns and Oliva, 1994 ). On the other hand, high spatial frequency representations of scenes do not generalize to unfiltered stimuli, suggesting that they may encode low-level differences rather than a categorical response.…”
Section: Discussionsupporting
confidence: 90%
“…Although the base architecture splits at the third stage of a CNN (e.g., ResNet), it does not mean that the two separate branches should never communicate with each other. As [11], [40] show that there exists connections and communications between LH and RH in the human brain, our LB and GB should also communicate with each other so that the features from two branches can complement and enrich each other. It will not get worse if we selectively leverage useful knowledge learned by the other branch to help the task of the current branch.…”
Section: B Gated Intercommunication Unitsmentioning
confidence: 99%
“…Although these deep learning models have advanced one step towards hemispheric specialization, they are still primitive in interhemispheric communications. As early as 1954, Tomasch and Joseph had already proposed that there exists connections and communications between LH and RH [40]; they also stated that this connective structure in the human brain is corpus callosum, which is the largest white matter structure in the human brain and consists of 200-300 million axonal projections [28]; Kauffmann et al also have indicated that LH and RH influence each other [11]. The corpus callosum plays an essential role in brain signal processing, e.g., it allows us to identify the objects we see by connecting the visual cortex with the language centers of the brain, and it also transfers tactile information between the brain hemispheres to enable us to locate touch.…”
Section: Introductionmentioning
confidence: 99%
“…Stimuli were 160 black-and-white photographs of scenes (256-level grayscales, 256 × 256 pixels) from the Labelme database (Oliva & Torralba, 2001), previously used in works of Kauffmann et al (2017) and Kauffmann, Bourgin, et al (2015). Scenes belonged to two distinct semantic categories: 80 man-made scenes (buildings, streets, highways) and 80 natural scenes (beach, open countryside, forests).…”
Section: Stimulimentioning
confidence: 99%